Sosialisasi Sistem Informasi Berbasis Android Untuk Penyuluhan Faktor Resiko Penyakit Jantung Koroner di Kantor Kecamatan Bontomarannu, Kabupaten Gowa - Zulkifli Tahir; Amil Ahmad Ilham; Muhammad Niswar; Adnan -; Zahir Zainuddin; Iqra Aswad; Zaenab -; Muhammad Alief Fahdal Imran Oemar (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
The Android is a Linux-based operating system designed for devices such as smartphones and tablet computers. An android-based information system has been developed through research work from the Department of Informatics, Hasanuddin University, together with a Clinical Nutrition Doctor, namely the application of detection for coronary heart disease. This is based on the fact that coronary heart disease is one of the most common cardiovascular causes of death in the world, claiming about 17.9 million people every year. The system can be used by the general public using a smartphone or tablet computer. In this service, we have carried out socialization to the public about this application as well as providing information about risk factors for coronary heart disease at the Bontomarannu sub-district office, Gowa Regency. The public is also given the application to be installed on their respective smartphone or tablet computers. The public around the sub-district was very enthusiastic about participating in this socialization event. With this socialization, the public can find out how to use the application and prepare for the prevention of the factors of coronary heart disease, what should be maintained or avoided.